A STUDY OF REGENERATION AND TRANSFORMATION COMPETENCE OF COTTON VARIETIES OF KAZAKH BREEDING - Rahimzhanova , A.O.; Kubash , Zh.A.; Ramankulov , Y.M.; Manabaeva , Sh.A. (Eurasian Journal of Applied Biotechnology, 2017)
Genetic modification of cotton is given special attention due to its high economic value. The control of weeds that have a negative impact on its yield is one of the main problems in agriculture. As a result, the genetic engineering has become an unavoidable tool for reducing the negative impact of herbicides, causing significant damage to field crops. The aim of this work was to study the regeneration processes, and also to obtain herbicide resistant cotton plants by using Agrobacterium-mediated transformation. A recombinant construct pBPAT-GFP containing the genes phosphinothricin acetyltransferase PAT and GFP was created. The regeneration features of Kazakhstani varieties of cotton such as Mahtaaral-4005, Turkestan-1, Atakent-2010 in tissue culture were studied and incompetence to shoot formation was revealed, however, a single case of the formation of primordia from the callus was observed with the combination of hormones 2,4-D and zeatin in concentrations of 0,5 mg/l and 0.2 mg/l, as well as 2iP and NAA in concentrations of 5.0 mg/l and 0.1 mg/l. An effective method for regenerating shoots from stem apical meristems of transformed plants has been developed. Intensive shoot formation of two-day apical meristems of cotton with the content of two phytohormones with cytokine activity of BAP and kinetin at a concentration of 2.0 mg/l was revealed.